A CROSS-SECTIONAL OBSERVATIONAL STUDY ON FETAL CONSEQUENCES OF JAUNDICE DURING PREGNANCY: INSIGHTS FROM A TERTIARY CENTRE IN BIHAR. - Gunjan, Gunjan; Kumar, Ashutosh; Kumari, Priyanka (Student’s Journal of Health Research Africa, 2024)
Background Jaundice during pregnancy poses significant risks to both maternal and fetal health, with potential complications including fetal jaundice, kernicterus, and stillbirth. Early detection and appropriate management are crucial to mitigate these risks. The study investigates the impact of jaundice during pregnancy on fetal outcomes within a tertiary centre setting in Bihar, aiming to enhance understanding and inform clinical management strategies. Methods The study included 200 pregnant patients with jaundice or deranged liver function tests during pregnancy. Demographic data, clinical features, obstetric complications, maternal and fetal outcomes, and maternal complications were assessed. Statistical analyses were performed to elucidate the relationship between jaundice during pregnancy and fetal outcomes. Results The study population had an average age of 28 years (± 4.5), with the majority being multiparous (65%). Common symptoms included yellowish discoloration of the skin and sclera (100%), pruritus (80%), dark urine (70%), and abdominal discomfort (60%). Obstetric complications such as intrauterine growth restriction (IUGR), hepatomegaly, and ascites were observed in varying proportions. Abnormal liver function tests were prevalent in 95% of cases, with elevated bilirubin levels (>2.5 mg/dL). Statistical analysis revealed a significant association between prolonged jaundice duration and adverse fetal outcomes such as IUGR, intrauterine fetal demise or stillbirth, and neonatal complications requiring immediate resuscitation (p < 0.05), with multiparity identified as a risk factor for maternal complications (p < 0.01). Conclusion Jaundice during pregnancy significantly impacts maternal and fetal health, necessitating vigilant monitoring and early intervention. The findings underscore the importance of timely management strategies to mitigate adverse outcomes, emphasizing the need for multidisciplinary collaboration in the care of pregnant patients with jaundice. Recommendations Recommendations include implementing standardized protocols for the management of jaundice during pregnancy, enhancing awareness among healthcare providers regarding the potential risks and complications, and fostering interdisciplinary teamwork to optimize maternal and fetal outcomes.